IDENTIFICATION OF REFERENCE GENES FOR GENE EXPRESSION ANALYSIS USING RT-QPCR IN PINELLIA TERNATA - H. Zhang; W. Zhang; S. Wei; Y. Xiong; X. Meng; Z. Zhang; Y. Duan; W. Sheng; T. Xue; J. Xue (Journal of Animal and Plant Sciences, 2023)
Pinellia ternata (Thunb.) Briet. is a well-known traditional Chinese herbal medicine that has many beneficial effects such as anti-tumor, anti-fertility, blood fat-reducing, and liver-protective. The comprehensive utilization value of P. ternata is high and the development prospect is broad. However, low tuber production resulting from “sprout tumble” (ST) due to high temperature and light intensity has largely reduced its use. Therefore, it is necessary to explore the functional gene responses to high temperature and light. Real-time quantitative PCR (RT-qPCR) is commonly used for accurately gene expression detection during gene function exploration. However, because the RT-qPCR results may vary depending on the conditions and environment, an internal reference gene (IRG) is needed to normalize the RT-qPCR data. Analyzing IRGs in P. ternata can help with subsequent functional characterization and verification of the genes regulating P. ternata growth. In this study, we screened 8 suitable IRGs, and determined the most suitable IRGs using the Ct value, GeNorm, NormFinder, and BestKeeper under shade and high-temperature conditions, and in different tissues. The results showed that 18S was a suitable IRG for P. ternata studies. This discovery has laid the foundation for further research on P. ternata, and is also beneficial for the exploration of more IRGs in medicinal plants.
Keywords: internal reference gene; high temperature; shade; RT-qPCR; Pinellia ternate